Design and construction of a STM for use in-situ in a TEM - Medford, Ben (2010)
Since its inception scanning tunneling microscopy (STM) has emerged as a powerful technique in the field of nanoscience, with applications that have provided extremely important insights into the local nano-scale chemical/electrical properties of semiconducting and conducting materials. However, this technique alone is not capable of directly observing the tip and sample during its operation. Direct observation of the dynamic changes of both the tip and sample may help to provide a better understanding of the mechanisms behind some STM applications. Recent developments in this area have successfully combined STM to operate in-situ with imaging techniques such as Scanning Electron Microscopy (SEM) and Transmission Electron Microscopy (TEM). This thesis presents a new design for an in-situ STM which can operate within the spatial confines of a TEM – allowing both techniques to be conducted simultaneously. To overcome the spatial constraints of imaging inside a TEM, the design uses a novel coarse approach mechanism; consisting of three parallel hammer-action inertial driving mechanisms that are attached via flexible linkages to a pivot plate that allows the STM tip to be reliably positioned to regions of interest in three dimensions. The operation of STM in a TEM provides numerous advantages that are not available with standard STM techniques; these advantages are discussed and potential applications for this technique are also presented. One such application investigated is the potential for using silver sulphide STM tips for use in in-situ STM manipulation.